1988
DOI: 10.1227/00006123-198807000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Extradural Hematoma: Analysis of Factors Influencing the Courses of 161 Patients

Abstract: The clinical and computed tomographic (CT) findings in a series of 161 consecutive patients operated upon for postraumatic extradural hematoma are analyzed. Thirteen (8%) patients had delayed epidural hematoma formation. The overall mortality for the series was 12%, significantly lower than that observed during the prior "angiographic" period at the same unit (30%). Because all but 1 of the deaths occurred among the 66 patients unconscious at the time of operation (27% mortality in this subgroup), the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(84 citation statements)
references
References 0 publications
2
61
1
20
Order By: Relevance
“…Yanaka et al (48), showed that greater hematoma volume and the thickness of SDH was associated with poor outcome and mortality. Many other authors reported similar findings for both EDH and SDH (11,22,30,45). We also demonstrated in our study that the larger the hematoma volume and the thickness, the higher the incidence of mortality and unfavorable outcome.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Yanaka et al (48), showed that greater hematoma volume and the thickness of SDH was associated with poor outcome and mortality. Many other authors reported similar findings for both EDH and SDH (11,22,30,45). We also demonstrated in our study that the larger the hematoma volume and the thickness, the higher the incidence of mortality and unfavorable outcome.…”
supporting
confidence: 52%
“…Pupils that are bilaterally unresponsive to light are associated with a high mortality (4,8,9,25,30,45). Patients with bilateral fixed and dilated pupils at surgery had 0-13% favorable outcome and 64-93% mortality rate (13,29,31,38,46).…”
mentioning
confidence: 99%
“…Kuday et al 25 observed a significant relationship between cranial fractures and adverse outcome in 115 patients undergoing surgery for EDH. Lee et al 27 did not see this relationship in a series of 200 patients managed similarly .But Rivas et al 28 reported a significantly lower mortality rate in patients with cranial fractures which is in strong agreement with our findings.…”
Section: 16supporting
confidence: 90%
“…The prognosis is nevertheless influenced by: age, degree of coma, pupillary reaction to light, size and site of haematoma and the mechanism of injury (Baykaner et al, 1988;Lobato et al, 1988). Delayed operative treatment of EDH is recognized as a poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%